People, change, values, and social and economic development proposed learning units in social studies III - Ordillas, Teresita Daus 1949- (1979)
The purpose of this study was to prepare learning units in social studies for third year high school on the concept of economic development and progress with the end in view of providing a model instructional material for social studies teachers. The writer has employed a content survey of library materials such as courses of study, learning units, magazines, books and other forms of publications on economic development of the Philippines and other countries. The main source was the social studies scope and sequence chart prepared by the Bureau of Public Schools, Ministry of Education and Culture.It was concluded that there is a great need for more quality instructional materials that reflect true Filipino spirit, sentiment, and tradition.